The History of the Chalcolithic Settlement in the Nahal Beer Sheva Area: The Radiocarbon Aspect - Gilead, Isaac 1948- (1994)
There are now dozens of 14C determinations from the Chalcolithic sites in the Nahal Beer Sheva area, most of them from the site of Shiqmim. The role of those dates, and stratigraphy, in establishing the history of the Chalcolithic settlement is described. Outlined also are the problems and prospects of defining phases of settlement by averaging sets of radiocarbon dates. The radiometric data suggest that the sites of Horvat Beter and Bir es-Safadi were settled centuries after Shiqmim was established. The article also illustrates that the radiocarbon dates cannot support the hypothesis that the subterranean structures in the Nahal Beer Sheva sites preceded the above-ground buildings.